Are Libraries Worth Investing in?: Finnish University Libraries and their Effect on the National Economy - Kiviniemi, Vesa; Laitinen, Markku; Saarti, Jarmo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
The paper discusses the correlation between the growth of the gross national product (GNP) of Finland and the library materials costs of the academic libraries during thirty years (1977–2006). Statistical data were used in the analysis and it was found that there is some correlation between the trends of these two. The paper discusses different possibilities for interpretation of this outcome, but the authors draw the conclusion that it is clearly worth investing in libraries as one tool to improve the knowledge economy.